Birth, sex and abuse: women's voices under Nazi rule - Chalmers, Beverley (Grosvenor House Publ., 2015)
"This book is a fascinating and gripping examination of birth, sex and abuse during the Nazi era. Dr Chalmers' unique lens on the Holocaust provides a stunning and controversial exposé of the voices of both Jewish and non-Jewish women living under Nazi rule. Based on twelve years of study, the book takes an inter-disciplinary view incorporating women's history, Holocaust studies, social sciences and medicine, in a unique, cutting-edge examination of what women themselves said, thought and did. Dr Chalmers (DSc(Med); PhD) has dedicated her life to studying women's experiences of giving birth in difficult social, political, economic and religious environments. During her distinguished academic career, she has held professorial appointments in both the Medical and Social Sciences and has served, for decades, as a maternal and child health consultant for numerous United Nations and other global aid agencies. Her inter-disciplinary focus and extensive international experience provide a novel perspective on the Nazi era and on the neglected issue of the Nazi abuse of childbearing and sexuality."--Publisher's description